Volume 4: Fluid-Structure Interaction 2007
DOI: 10.1115/pvp2007-26157
|View full text |Cite
|
Sign up to set email alerts
|

An Acoustic Criterion for the Whistling of Orifices in Pipes

Abstract: Whistling due to vortex shedding has been extensively studied in the case of cylinders in cross-flows, of flow separation above cavities and of shear layers with flow impingement feedback. Less attention has been given to pressure drop devices in piping systems, which are known to generate high noise levels due to single tones in gas systems, and even in water systems. Based on recent work of Auregan et Starobinski (1999), an experimental criterion is proposed to evaluate the whistling ability of a pressure dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…The arguments of the extradiagonal elements have not been plotted, because their modulus are smaller than 0.1. The transmission and reflection coefficients of the original scattering matrix appear to reasonably fulfill the low Mach number relations, [20][21][22] namely…”
Section: A Acoustic Amplification In Linear Regimementioning
confidence: 92%
See 2 more Smart Citations
“…The arguments of the extradiagonal elements have not been plotted, because their modulus are smaller than 0.1. The transmission and reflection coefficients of the original scattering matrix appear to reasonably fulfill the low Mach number relations, [20][21][22] namely…”
Section: A Acoustic Amplification In Linear Regimementioning
confidence: 92%
“…In the latter case, the fluid compressibility inside the orifice does not play a significant role, and the four elements of the scattering matrix are no longer independent. [20][21][22] Benefiting from this circumstance, a new set of variables can be introduced, which facilitates the physical understanding of acoustic amplification and of pure tone generation.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, Moussou et al (2007) investigated experimentally a long pipe fitted with a constriction for a number of values of the constriction ratio and the thickness ratio β. They observe that the conditional instability criterion Z R > 0 (or arg(B) > π/2 using their notation) is verified in a range St L ≈ [0.2, 0.25], again in good agreement with the C1 conditional instability frequency range.…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
“…Fabre et al (2020, § 8). Moussou et al (2007) studied experimentally a long pipe with a constriction for a number of values of the constriction ratio and the thickness ratio. In this study, they identified both the first and second branch of conditionally unstable modes.…”
Section: Introductionmentioning
confidence: 99%